Application of Liquid-Based Cytology to Fine-Needle Aspiration Biopsies of the Thyroid Gland - Fadda, Guido (Frontiers in Endocrinology, 2012)
FNAB (fine-needle aspiration biopsy) is regarded as an important tool for diagnosing thyroid lesions because of its simplicity, safety and cost-effectiveness. Its role in correctly characterizing the group of indeterminate lesions or follicular-patterned neoplasms (FN) might be more decisive. LBC (Liquid-based cytology) is a technique based on the use of a semi-automated device that has gained popularity as a method of collecting and processing both gynecologic and non-gynecologic cytologic specimens. It achieves a diagnostic sensitivity as accurate as conventional preparations especially for its excellent cell preservation and for the lack of background which decrease the amount of inadequate diagnoses. Moreover, the cellular material which has been stored in the preservative solution could be effectively used for the application of immunocytochemical and molecular techniques used especially for the Follicular proliferations . In many cases the cytologic features are similar in both methods but the colloid film and the lymphocytic component are more easily evaluated on direct smears whereas nuclear details and colloid globules are better evaluated in LBC slides. The LBC processed biopsies represent a valid alternative to conventional cytology. The possibility of applying special techniques enhance the efficacy of the cytological diagnosis of thyroid lesions.